Oral Molnupiravir and Nirmatrelvir/Ritonavir for the Treatment of COVID-19: A Literature Review with a Focus on Real-World Evidence - Ioannis Karniadakis; Nikolaos Mazonakis; Constantinos Tsioutis; Michail Papadakis; Ioulia Markaki; Nikolaos Spernovasilis (MDPI AG, 2023)
Vaccines remain the cornerstone of medical prevention and are highly effective in reducing the risk of severe disease and death due to coronavirus disease 2019 (COVID-19). In the context of expanding the therapeutic armamentarium against COVID-19, molnupiravir (Lagevrio) and ritonavir-boosted nirmatrelvir (Paxlovid) were developed, constituting the first effective oral treatments against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this narrative review, we retrospectively inquired into the clinical trials and real-world studies investigating the efficacy of these agents. Overall, clinical trials and real-world studies have demonstrated the efficacy of both agents in reducing hospitalization and death rates in COVID-19 patients. As per current recommendations, their use is suggested in patients with mild to moderate symptoms who are at high risk of developing severe disease. Nevertheless, limited data exist regarding their efficacy in specific subpopulations, such as immunocompromised patients, those with severe kidney disease, pregnant women, and children.